Implementasi Pembelajaran Jasmani Dan Olahraga Dengan Model Pendekatan Kooperatif Dan Permainan Di Sekolah Dasar - Ika Pra Sauma; Livia Aliyah Alfita; Rida Nazmi Farhani; Rifa Fauziah Kamal; Sofian Putri Lumban Gaol; Zahra Amanda Koswara; Agus Mulyana (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine how the Cooperative Approach and the use of games can increase students' interest in learning physical and sport at Primary School. Learning interest in PE is an important factor in improving learner engagement and achievement. The game learning model and the Cooperative Approach are the focus of this study because this approach emphasizes cooperation and social interaction between learners. The method used in this research is a qualitative method with literature study. The literature study was conducted by searching and analyzing relevant sources regarding the implementation of Sports and Physical learning using games and the Cooperative Approach to increase students' interest in the learning process at elementary schools. Learners tend to show higher motivation, more active engagement and greater interest in learning with game models and cooperative approaches. This research provides a comprehensive understanding of the effect of Game Model Learning and Cooperative Approach on learners' interest in learning through literature review.